Analisis Kepuasan Wisatawan Terhadap Objek Wisata Religi Masjid Al-Kahfi Kabupaten Kaur - Alpiyan Oktori; Eka Sriwahyuni; Aan Shar (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to determine the satisfaction of tourists visiting the religious tourism of the Al-Kahfi grand mosque in the southern kaur district of the kaur district, and what factors make tourists interested in visiting the religious tourism of the Al-Kahfi grand mosque. This research uses qualitative methods. Informants in this study amounted to 10 people. Secondary data and additional data were taken in the form of information that would complement primary data. Data collection techniques are observation, interview and documentation. The results of this study can be concluded that tourists who visit feel quite satisfied, because tourists interested in visiting again are families who have children. Willing to recommend the tours visited, to friends, relatives, and neighbors because tourists feel that the existing facilities and infrastructure are complete. location and access are easy for all transportation to pass, have a large parking lot and the local environment supports the existence of religious tourism. As well as a comfortable and cool environment and friendly local people make tourists feel at home and linger in the religious tourism of the Al-Kahfi grand mosque. Keywords: expectation conformity, visiting interest, recommend.